Treacherous Sands: The EU and Terrorism in the Broader Sahel. Issue 2 (December 2014) - Korteweg, Rem
In the Sahel weak government institutions, porous borders, and ethnic, religious and tribal tensions enable organised crime networks, militants and terrorist groups to operate with relative impunity. The region is now a transmission belt for instability across resource-rich northern Africa. Lucrative hostage deals and smuggling have created a close relationship between organised crime and terrorist networks. Turmoil in the Sahel influences, and is influenced by, the aftermath of the Arab revolutions. European citizens and interests are at risk. The EU has a strategy to promote security and development in the Sahel, and its military missions focus on capacity-building to stem the terrorist threat. However, the EU does not have an integrated approach to the broader Sahel.